2011
DOI: 10.1097/icu.0b013e32834994a0
|View full text |Cite
|
Sign up to set email alerts
|

The current state of ptosis repair

Abstract: The recent preference for posterior approach ptosis surgery, in particular the MMCR, is multifactorial. In order to understand the evolution of opinions about the procedure, a historical knowledge of involutional ptosis and ptosis repair is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…Each technique has its indications as well as its specific types of complications. 29 30 31 32 Experience is a great teacher and will help the surgeon determine which surgical approach will give the best outcome for a given patient. The most common techniques involve advancing or reattaching the levator aponeurosis, resecting a portion of Müller's muscle and conjunctiva (MMCR technique) or connecting the eyelid directly to the frontalis muscle by autologous tissue (e.g., fascia lata) or nonautologous material (e.g., silicone rods, polytetrafluoroethylene/Gore-Tex suture).…”
Section: Tablementioning
confidence: 99%
“…Each technique has its indications as well as its specific types of complications. 29 30 31 32 Experience is a great teacher and will help the surgeon determine which surgical approach will give the best outcome for a given patient. The most common techniques involve advancing or reattaching the levator aponeurosis, resecting a portion of Müller's muscle and conjunctiva (MMCR technique) or connecting the eyelid directly to the frontalis muscle by autologous tissue (e.g., fascia lata) or nonautologous material (e.g., silicone rods, polytetrafluoroethylene/Gore-Tex suture).…”
Section: Tablementioning
confidence: 99%
“…The amount of resection/tacking can be small (10–13 mm), medium (14–20 mm) or large (21–26 mm) and can be tailored to be smaller or larger depending on the levator function. The procedure can be carried out via anterior or posterior approach [ 51 ].…”
Section: Upper Eyelid Dermatochalasis and Ptosismentioning
confidence: 99%
“…Various brow/frontalis suspension techniques either with autogenous or banked fascia lata or alloplastic material (mersilene, mash, silicone rod) are available [ 51 ], [ 52 ], [ 53 ]. Although many autoplastic and alloplastic material have been proposed it is generally agreed that fascia lata gives the best results.…”
Section: Upper Eyelid Dermatochalasis and Ptosismentioning
confidence: 99%
“…9,10 The past decades the posterior approach for involutional ptosis repair has gained preference over the anterior approach. 1,2 Several factors contributed to the resurgence of the MMCR, including the predictability, the shorter operating time and the proposed mechanism of action. 1,2 Although external levator advancement (ELA) and MMCR are equally effective in correcting blepharoptosis, MMCR yields a better cosmetic outcome and causes less eyelid asymmetry.…”
mentioning
confidence: 99%
“…1,2 Several factors contributed to the resurgence of the MMCR, including the predictability, the shorter operating time and the proposed mechanism of action. 1,2 Although external levator advancement (ELA) and MMCR are equally effective in correcting blepharoptosis, MMCR yields a better cosmetic outcome and causes less eyelid asymmetry. 1,3 Levator plication and vertical shortening of the posterior lamella are pervasive theories on the mechanism of action, although a recent study found arguments against a purely mechanical mechanism of the MMCR.…”
mentioning
confidence: 99%